Pelaksanaan Program Kampus Mengajar di SD Negeri 12 Rufei Kota Sorong - Rahma Rahma; Marissa S. Tupamahu; Dian Saputra, M.Pd; Ahmad Wael; Kris Uluelang (LP3M Universitas Muhammadiyah Sorong, 2023)
Kampus Mengajar is a learning and teaching activity in the basic education unit of the Merdeka Belajar Kampus Merdeka (MBKM) to provide learners with opportunities to take classes elsewhere for one semester and practice their ability to solve complex problems by becoming partner teachers to innovate in learning, developing creative, innovative, and fun strategies and learning models. Students gain experience exploring various programs based on SD Negeri 12 Kota Sorong's needs, honing leadership skills, problem-solving during program activities, interpersonal abilities with school principals, teachers, and students, analytical thinking, creativity, and innovation directly from the field. How to be concise in carrying out the tasks required by the placement school. Students' duties within the teaching campus program include supporting the educational process, assisting school administration, participating in technological adaption, reading, and numeracy, and assisting with incidental school events. Students also do self-evaluations, compose and post final activity reports, and conduct self-evaluations/assessments alone and in groups. Learners that participate in this program may improve their social skills and become more mature about how to learn to be excellent instructors even if they have restricted talents.